1987
DOI: 10.1136/gut.28.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Histologic differential diagnosis of focal liver lesions by ultrasonically guided fine needle biopsy.

Abstract: On fine needle histological sampling tissue fragments are obtained, making possible a histological diagnosis with a more precise tumour description. The purpose of our study was to examine the differential diagnostic value of ultrasonically guided fine needle aspiration combined with histological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…21 However, FNB is a procedure that enables FLLs to be diagnosed accurately, with an overall accuracy of 90% to 95%, 6-10 a sensitivity of 85% to 90%, 3,8 and a specificity of 100%. 8,9 Recent studies using new techniques for sampling (2) 61 (61; 53-69) Hemangiomas (3) 27.7 (34; 14-35) Not correctly diagnosed (4) 17.8 (19.5; 6-26) NOTE. The statistical test used for performing analysis of variance was a unilateral F-test with the P value set at .5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, FNB is a procedure that enables FLLs to be diagnosed accurately, with an overall accuracy of 90% to 95%, 6-10 a sensitivity of 85% to 90%, 3,8 and a specificity of 100%. 8,9 Recent studies using new techniques for sampling (2) 61 (61; 53-69) Hemangiomas (3) 27.7 (34; 14-35) Not correctly diagnosed (4) 17.8 (19.5; 6-26) NOTE. The statistical test used for performing analysis of variance was a unilateral F-test with the P value set at .5.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is generally accepted that in most cases, fineneedle biopsy (FNB) is safe, accurate, and enables a definitive diagnosis to be made quickly. [3][4][5][6][7][8][9][10] However, some problems, such as the well known possibility of neoplastic seeding 11,12 and the conflicting results of diagnosis in patients with well-differentiated hepatocellular carcinomas (HCCs) [13][14][15] and benign tumors, 1,16 represent limitations that should be considered further. In particular, precise details of the prevalence of tumor cell seeding along the needle tract have yet to be determined, despite the fact that this problem is real 17 and its occurrence leads to a worse prognosis.…”
mentioning
confidence: 99%
“…Histology is the gold standard in the differentiation of liver lesions. It is accepted that in most cases, percutaneous biopsy is safe, accurate, and enables a definitive diagnosis to be made quickly [7][8][9]. However, some problems, such as the possibility of neoplastic seeding, present limitations [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that ultrasonically guided percutaneous fine needle biopsy is highly accurate and is rarely associated with fatal complications (41,42). With regard to biopsy specimens, tumor heterogeneity and unsteady VEGF expression within the same lesion may represent potential biases in our results.…”
Section: Discussionmentioning
confidence: 99%